Association of H. pylori infection indicated by their serum IgG antibodies with lymphoma malignancy - Zeki Ali Mohamed (Zanco Journal of Pure and Applied Sciences, 2020)
Lymphoma is a type of lymphocyte malignancy that develops in different types of lymphoid tissues, many pathogens are expected to be implicated in the establishment of the disease including Helicobacter pylori (H. pylori). A total of 64 B-cells lymphoma patients recruited to oncology-hematology unit in Azadi Teaching Hospital in Duhok city and 60 sex and age matched apparently healthy individuals were involved in the current study. Serum samples were collected from all subjects and tested for detecting IgG antibodies against H. pylori as an indicator for H. pylori infections. The age average was (52.5±12.4) years for lymphoma cases and (56±12.5) years for controls. IgG anti-H. pylori antibodies were found in 11/64 (17.9%) of the lymphoma patients and in 8/60 (13.3%) of the control subjects. Lymphoma cases younger than 80 years had higher prevalence of IgG anti H. pylori antibodies (28.6%) as compared with all other age categories with a significant increase compared to both age groups ˂40 years (p= 0.008), 51-60 years (p=0.04) and 61-70 years (p=0.02) respectively. No significant difference was found in the IgG anti H. pylori antibodies prevalence between the lymphoma and control subjects (p=0.087), the gender had no significant effect on the IgG anti H. pylori antibodies prevalence in both of the lymphoma and control subjects respectively and between the two groups. Based on OR=1.34 (95% CI= 0.49-3.42) a very weak association of IgG anti H. pylori antibodies prevalence was observed with an overall increased risk of lymphoma. In conclusion, a week association of H. pylori infection with lymphoma was found due to non categorization of the lymphoma cases pathologically, the association might increases significantly if being categorized pathologically.